1251 Management Considerations in an Adolescent with Kleine-Levin Syndrome. (27th May 2020) - George, Alisha; Chopra, Nikki; Afolabi-Brown, Olufunke
Abstract: Introduction: Kleine-Levin syndrome (KLS) is a central disorder of hypersomnolence characterized by recurrent episodes of excessive sleepiness and sleep duration, along with varying degrees of cognitive dysfunction, altered perception, disinhibited behaviors, and eating disorders. Individuals with KLS are reported to be asymptomatic between episodes. KLS has a male preponderance with symptom onset typically during adolescence. A genetic basis has been suggested due to clustering of cases in certain ethnic populations and families. Purported triggers include viral infections, physical exertion, head trauma, and sleep deprivation. Report of Case: A 15-year old male developed sudden-onset hypersomnolence with sleep duration of 20-23 hours per day. While awake, he had altered mentation and personality changes; parents reported aggression, hypersexual behaviors, hyperphagia, and derealization. During this 2-week episode, he underwent an extensive, yet unrevealing work-up and eventually experienced symptom resolution. Over 16 months, he has had 5 discrete episodes of hypersomnolence with abnormal wake behaviors, all preceded by viral illnesses and/or significant physical exertion and felt to be consistent with KLS. He has reported ongoing, albeit less severe, excessive daytime sleepiness between episodes. Polysomnography and multiple sleep latency testing, both performed while asymptomatic, were largely unremarkable. As episodes have decreased in duration and intensity over time, trials of lithium and stimulant therapy have been deferred per family preference, though the patient was started on a short course of azithromycin during his last episode for anti-inflammatory properties. Notably, the patient has developed significant anxiety due to fear of recurrence and is now engaged in therapy. Conclusion: KLS is a rare disorder that tends to have shorter and less severe manifestations over time. To date, very few systematic studies have been done to evaluate potential treatments, such as lithium and macrolide therapy. Avoidance of triggers and adequate sleep are encouraged, and mental health support should also be considered.